Interstitial literatures: contemporary North American writing and uneven development 1990-2015 - Cooper, Samuel J. (2020)
This thesis is an intervention into the burgeoning field of geocritical literary studies. It uses Henri Lefebvre’s theory of the production of space to develop socio-spatial readings of contemporary poetry and novels and argues that these texts present a distinctly neoliberal spatiality. The thesis follows Michel Foucault in conceiving of neoliberalism as an order of normative reason, and suggests that it applies economic values and metrics to every aspect of life. It argues that uneven development is the socio-spatial manifestation of the economic logic of competition that lies at the heart of neoliberalism. These neoliberal spaces act to reveal inequality rather than conceal it as capitalism hitherto tended to. Unevenness comes to represent functional competition. The interstitial literatures under study in this thesis self-reflexively register uneven development in their form and content to explore the implications of, and possibilities of resistance to, a world made increasingly economic.